Sunbul Haqiqi’s poetic experience (Raparin Journal of Humanities (RJH), 2023)
This research is about Sunbul Haqiqi’s poetic works which is a descriptive and analytical research. The reason behind choosing this subject is the lack of a scientific and academic research about her poems. The aim of this research is to show her poetic works and identify the various components of the poems of the poet in terms of content and formThe research includes an introduction، two chapters and a conclusion:      Chapter one is Sunbul and poetry، and it consists of two parts: in the first part، it talks about the most important stages of her life، and in the second part، the focus is on the poet and poetry، and it refers to the poet’s relationship with poetry.                                                                                 Chapter two includes Sunbul’s poems in terms of form and content، and it also consists of two parts: in the first part، it talks about the form of the poet’s poems، and in the second part، the concentration is on the content of the poet’s poems.                                                                                     In the end، it shows the most significant points that we have reached. Then the list of resources and a summary of the research in two languages، Kurdish and Kurdish have been recorded.